1989
DOI: 10.1149/1.2097375
|View full text |Cite
|
Sign up to set email alerts
|

Hexachlorodisilane as a Precursor in the LPCVD of Silicon Dioxide and Silicon Oxynitride Films

Abstract: Films of silicon dioxide and silicon oxynitride were grown by LPCVD using gas‐phase mixtures of Si2Cl6 , N2O , and NH3 in the temperature range 550°–850°C. The activation energy for SiO2 deposition was 29 kcal/mole. Under comparable pressure and temperature conditions, growth rates of SiO2 from Si2Cl6 were at least three times higher than those obtained using SiH2Cl2 or SiH4 . The effect of temperature and reactant flow ratios on film composition, stress, refractive index, etch rate, and uniformity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…1(a) had a shift of about 60 cm À1 towards low wavenumbers, and the disappeared N-H vibration peaks at 3380 and 1175 cm À1 showed a good ceramization of the preceramic polymer. Additionally, the strong absorbance peak at 831 cm À1 was near the Si-N stretching mode of Si 3 N 4 at 840 cm À1 [6], confirming the presence of PHPS-derived silicon nitride matrix in the asreceived composite. When annealed at elevated temperatures (1400 and 1600 1C), the absorption peak for residual Si-H bonding in the composite became weaker, and the sharp peaks at 1099 cm À1 and 831 cm À1 became blunt.…”
mentioning
confidence: 61%
“…1(a) had a shift of about 60 cm À1 towards low wavenumbers, and the disappeared N-H vibration peaks at 3380 and 1175 cm À1 showed a good ceramization of the preceramic polymer. Additionally, the strong absorbance peak at 831 cm À1 was near the Si-N stretching mode of Si 3 N 4 at 840 cm À1 [6], confirming the presence of PHPS-derived silicon nitride matrix in the asreceived composite. When annealed at elevated temperatures (1400 and 1600 1C), the absorption peak for residual Si-H bonding in the composite became weaker, and the sharp peaks at 1099 cm À1 and 831 cm À1 became blunt.…”
mentioning
confidence: 61%
“…The unpredictability in the formation of the shock sensitive hydrolysis products has made the study of the shock sensitivity of the materials difficult. However, understanding of the mechanism of the shock sensitivity has become important for safe handling of these hazardous materials in the manufacture of HCDS, as this molecule is being adopted as a universal precursor for chemical vapor deposition or atomic layer deposition of silicon-containing semiconductor or dielectric thin films. …”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that high quality silicon oxynitride films can be deposited using Si 2Cl 6 (hexachlorodisilane) as a precursor (44). The rate of film growth above 550·C and at 1 Torr was observed to be significantly higher than that obtained with more conventional precursors such as monosilane and disilane.…”
Section: Silicon Oxynitridementioning
confidence: 96%